ANFIS Control Strategy for DC fast charging of micro grid connected vehicle - Akula Madhu Sree; P.Kiran Kumar; Velappagari Sekhar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper we proposes a ANFIS Control Strategy for DC fast Charging of Micro grids. ANFIS Controller gives better performance when compared along with PI, Fuzzy Logic Controller. An Appropriate framework and control frameworks must be created all together to understand this idea. Electric vehicle batteries could be utilized as potential vitality stockpiling gadgets in the micro grid, when there is excess of Grid-To-Vehicle and provides vitality back to the network V2G when it is required. Design for actualizing a V2G-G2Vframework in a miniature network utilizing level-3 type of quick charging of EVs is introduced in this paper. A miniature network test framework is demonstrated in which it contains a dc quick charging station for the interfacing of the Electric vehicles. Reproduction examines are done to show V2G-G2V power move. The simulation outcomes shows a dynamic force guideline in the miniature matrix by EV batteries through G2V-V2G methods of activity. The charging station configuration guarantees negligible consonant contortion of lattice infused current and the regulator givesgood dynamic performance in terms of dc bus voltage stability, stability and reduces harmonic distortions.